Одабрани криминолошки аспекти преварне трговине кроз лажне менаџере (International Journal of Contemporary Security Studies, 2021)
The aim of the presented article is to point out at the CEO frauds (Chief Executive Officers´ crimes committed through the instruction of the so-called "false manager") as a relatively new and serious form of crime. The analysis of reports of unusual business operations showed that the most common cases of money-laundering and their connection to predictive crime in 2018 included (among others) CEO frauds. The crime in question is viewed from the perspective of criminology. The theoretical part of the paper points out at the criminal law dimension, phenomenology, perpetrators and their modus operandi, objects of such fraud or possible prevention. The above-mentioned part of the paper is also supplemented by real cases from application practice in the form of case reports. The findings of the Financial Intelligence Unit and the Criminal Police Office of the Slovak Republic, as well as professional literature and legal documents, were used to summarize the information.
Keywords: frauds; CEO frauds; money-laundering; unusual business operations; Financial Inteligence Units; Criminal Police Office; Slovakia